MANIFESTASI PEMBANGUNAN EKONOMI NASIONAl MENCAPAI BANGSA YANG SEJAHTERA - Asep Hidayat; Cinta Amalia Putri (JISOS: JURNAL ILMU SOSIAL, 2024)
The purpose of this writing is motivated by an incident or event that makes the author conduct a study. The author finds a number of facts regarding the quality of the country's infrastructure in economic, social and educational aspects in Indonesia. Therefore, on this occasion the author describes the ideal role to realize the country's development infrastructure in order to achieve a prosperous nation through several stages and strategies that must be realized by state officials or public officials. In this writing, the research method carried out is referring to a qualitative approach that refers to the study of literature. The results of the study explain that the best strategy in improving the quality of state development infrastructure is the best collaboration between the state apparatus and the community